1993
DOI: 10.1090/s0002-9947-1993-1182980-3
|View full text |Cite
|
Sign up to set email alerts
|

The geometry of Julia sets

Abstract: Abstract.The long term analysis of dynamical systems inspired the study of the dynamics of families of mappings. Many of these investigations led to the study of the dynamics of mappings on Cantor sets and on intervals. Julia sets play a critical role in the understanding of the dynamics of families of mappings. In this paper we introduce another class of objects (called hairy objects) which share many properties with the Cantor set and the interval: they are topologically unique and admit only one embedding i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
111
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(113 citation statements)
references
References 14 publications
1
111
1
Order By: Relevance
“…In [11], the existence of so-called Cantor bouquets in the Julia set was proved for a number of families of entire maps from B, including the exponential and sine families from Example 1. In [1], Aarts and Oversteegen showed that for these two families the Julia set is homeomorphic to so-called straight brush in the plane. In particular, each hair is homeomorphic to the half-line [0, ∞).…”
Section: Theorem B a Riemann Map Onto B Has Radial Limits At All Poinmentioning
confidence: 99%
See 1 more Smart Citation
“…In [11], the existence of so-called Cantor bouquets in the Julia set was proved for a number of families of entire maps from B, including the exponential and sine families from Example 1. In [1], Aarts and Oversteegen showed that for these two families the Julia set is homeomorphic to so-called straight brush in the plane. In particular, each hair is homeomorphic to the half-line [0, ∞).…”
Section: Theorem B a Riemann Map Onto B Has Radial Limits At All Poinmentioning
confidence: 99%
“…Take z ∈ X 1 ∩ X 2 . Then z = lim n→∞ z (1) n = lim n→∞ z (2) n for some z -sup z∈ω X dist(z, X), sup z∈ω Y dist(z, Y) < ε for a small ε > 0, -ω X (0), ω Y (0) ∈ 1 , ω X (1), ω Y (1) ∈ 2 , -Re(ω X (t)), Re(ω Y (t)) ∈ (R 1 , R 2 ) for t ∈ (0, 1),…”
Section: Lemmamentioning
confidence: 99%
“…following Aarts and Oversteegen [1], a Cantor bouquet is any planar set that is homeomorphic to a straight brush. To define this set, let B be a subset of [0, ∞) × I where I is a dense subset of the irrational numbers.…”
Section: Cantor Bouquets and The Complex Exponentialmentioning
confidence: 99%
“…In the limit, the set of points which do not fall into H after some iterate of E λ is the Julia set of E λ , J (E λ ), and it is known that this set consists of infinitely many curves, each with a distinguished endpoint and a "stem", i.e., the portion of the curve that extends from the endpoint to ∞ in the right half plane. This is the Cantor bouquet [1,9].…”
Section: Cantor Bouquets and The Complex Exponentialmentioning
confidence: 99%
“…The problem is to show that R n t;g is a Cantor bouquet [1,5]. For this, it is needed to know more about the endpoints of the closed half lines in R n t;g , in particular, one has to prove that the set of endpoints accumulates on every point of R n t;g .…”
Section: The Problemmentioning
confidence: 99%